Carbon-based pumice stone and preparation method thereof

By using materials such as sludge or organic sludge to prepare carbon-based pumice with honeycomb pipeline bundle structure, the problems of low effective porosity of existing filter materials and high cost of activated carbon are solved, efficient adsorption and flowability are achieved, and cost is reduced. .

CN119462075AActive Publication Date: 2025-02-18SHENZHEN WUBEN MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411671724.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The effective porosity of the filter material in existing water treatment is low and it is prone to clogging. At the same time, the raw material cost of activated carbon is high, resulting in excessive overall cost.

Method used

Sludge or organic sludge is used as the basic material, combined with silicon-aluminum formulation agent and auxiliary carbon source, and through foaming and sintering processes, carbon-based pumice stone with honeycomb pipeline bundle structure is formed to improve its effective porosity and adsorption performance.

Benefits of technology

It significantly improves the effective porosity and adsorption performance of carbon-based pumice, reduces manufacturing costs, reduces the probability of blockage, and improves the conductivity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462075A_ABST
    Figure CN119462075A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-based pumice stone and a preparation method thereof, and belongs to the technical field of new material preparation in water treatment. The base material and / or the silica-alumina ratio blending agent are / is used as the main material, the foaming agent and the foaming promoter generate a large number of bubbles during foaming, and a large number of open pores and gaps are formed in the material, so that the effective porosity is improved; a gas-retaining agent is adopted to wrap the material, so that generated bubbles are prevented from quickly escaping, and the effective porosity is further improved; cO generated by organic carbon and biochar is deoxidized into pure elemental carbon molecules by sintering under a sealed condition, and meanwhile, a honeycomb-shaped pipeline bundle structure consisting of carbon molecules is formed by self-assembly in a pre-manufactured gap, so that the adsorbent has excellent adsorbability and liquidity; by adopting sludge or organic sludge and a small amount of auxiliary carbon sources, a structure which takes silicon oxide as a main body and contains honeycomb-shaped carbon molecule pipeline bundles connected with a large number of air holes is obtained, the performance of the material is greatly improved, meanwhile, the use of a large number of wood materials is reduced, and the cost of raw materials is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new material preparation in water treatment, and particularly relates to a carbon-based pumice and a preparation method thereof. Background Art

[0002] In water treatment projects, filter tank is a common process technology, and the filter media in the filter tank is a very important link. The commonly used porous materials for filter media are pumice and activated carbon.

[0003] At present, most filter materials in water treatment are made porous on the surface, and the porous specific surface area is used to absorb organic matter in the water. The effective porosity is low, and the liquid only flows in the gaps between the materials, which can easily lead to blockage due to lack of permeability or poor permeability.

[0004] The porosity of pumice and activated carbon is mostly calculated by mass ratio, which has a very high upper limit, sometimes up to 200% to 400%. However, in actual water treatment, the effective porosity (volume ratio) is often obtained by volume calculation (Formula I).

[0005] The calculation formula of the effective porosity of the filter material at room temperature is shown in Formula I, which is described by volume ratio:

[0006]

[0007] In the formula, m1 is the mass of the material when dry, m2 is the mass of the material after saturation with water, and V1 is the volume of the material.

[0008] The theoretical upper limit of the volume ratio is 100%. The effective porosity can be better reflected in real projects and can be truly used in projects to test the water storage capacity and pollutant adsorption capacity of materials.

[0009] In addition, pumice has a certain porosity and a large specific surface area. There are pores inside it that can store some water. Pumice is divided into natural pumice and artificial pumice. Artificial pumice has a high effective porosity of 20-30%; the effective porosity of natural pumice is 5-20%. The activated carbon commonly used in water treatment is coconut shell activated carbon (effective porosity 30-40%) and coal activated carbon (effective porosity 20-30%). The effective porosity of both filter materials is low. Pumice and activated carbon have closed pores inside, which cannot realize liquid flow, and there is still blockage. In addition, the cost of raw materials for making activated carbon is too high, resulting in its overall cost being too high, so it has not been used in large quantities. Therefore, how to improve the adsorption performance and fluidity of filter materials and reduce costs has become a technical problem that needs to be solved in this field. Summary of the invention

[0010] The purpose of the present invention is to provide a carbon-based pumice and a preparation method thereof. Compared with conventional activated carbon materials, the carbon-based pumice provided by the present invention has better effective porosity, adsorption performance and conductivity, and can significantly reduce the manufacturing cost.

[0011] Traditional carbon-based materials are basically made of a large amount of wood and coal-based materials through various methods, and finally prepared into finished products with carbon as the main body. Typical representatives are wood activated carbon, coconut shell / fruit shell activated carbon and coal-based activated carbon.

[0012] The present invention is a mixture of silicon-based materials and carbon-based materials. It uses silicon oxide in sludge as the main basic material, and is supplemented by silicon-aluminum blending agents to form the main body. It uses special foaming agents and gas retaining agents to create a large number of pores and gaps inside the material; and uses organic matter in sludge as the main carbon source and adds a small amount of auxiliary carbon source. In a sealed space, carbon molecules are reduced, and after deposition, the carbon molecules self-assemble in the pre-made gaps to form a honeycomb pipe bundle structure composed of carbon molecules. These bundle-structured pipes give the material good adsorption and flowability, and also give it good conductivity. At the same time, silicon oxide molecules provide it with good stability and strength.

[0013] The carbon-based pumice prepared by the preparation method provided by the present invention has a honeycomb pipe bundle structure, which is different from the structure of existing filter materials. This structure can enable the material to have excellent adsorption performance and conductivity, both of which exceed the conventional activated carbon materials currently on the market. At the same time, silt or organic sludge is used as a basic material and a small amount of auxiliary carbon source to prepare a structure with silicon oxide as the main body and containing honeycomb carbon molecular pipe bundles connecting a large number of pores. While improving the performance, it reduces the use of a large amount of wood materials, saves the cost of raw materials, and makes its manufacturing cost much lower than that of conventional activated carbon materials.

[0014] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0015] The present invention provides a method for preparing carbon-based pumice, comprising the following steps:

[0016] (1) mixing a main material, a foaming agent, a foaming aid and water to obtain a slurry; the main material comprises a base material and / or a silicon-aluminum ratio adjusting agent; the base material comprises sludge or organic sludge;

[0017] (2) granulating the slurry obtained in step (1) to obtain spherical particles;

[0018] (3) spraying an aqueous solution of an air retaining agent onto the surface of the spherical particles obtained in step (2), and then foaming and drying the particles in sequence to obtain a blank;

[0019] (4) performing a first sintering on the blank obtained in step (3) under a sealed condition to obtain a first sintered product;

[0020] (5) subjecting the first sintered product obtained in step (4) to a second sintering in a nitrogen atmosphere to obtain a second sintered product;

[0021] (6) Activating the second sintered product obtained in step (5) to obtain carbon-based pumice.

[0022] Preferably, the silicon-aluminum ratio adjusting agent in step (1) is Al 4 [Si 4 O 10 ][OH] 8 The purity of the silicon-aluminum ratio adjusting agent is above 95%, and the particle size of the silicon-aluminum ratio adjusting agent is 200-300 meshes.

[0023] Preferably, in step (1), the foaming agent is azodicarbonamide and / or polyurethane, and the foaming agent accounts for 0.5 to 1.5% of the mass of the main material.

[0024] Preferably, in step (1), the foaming aid is at least one of calcium carbonate, calcium bicarbonate, aluminum chloride and phosphate starch, and the mass ratio of the foaming aid to the foaming agent is 1:1.

[0025] Preferably, the air retaining agent in step (3) is sodium silicate and / or methyl cellulose, and the mass concentration of the aqueous solution of the air retaining agent is 1 to 3%.

[0026] Preferably, the foaming temperature in step (3) is 150-200° C., and the foaming time is 30-60 min.

[0027] Preferably, in the step (4), the temperature of the first sintering is 1000-1200° C., and the time of the first sintering is 90-120 min.

[0028] Preferably, the temperature of the second sintering in step (5) is 1000-1200°C, and the time of the second sintering is 30-60 minutes.

[0029] Preferably, the activator used for activation in step (6) is an aqueous solution of at least one of biological acid, sodium lauryl sulfate, fatty alcohol polyoxyethylene ether and alkyl glycoside.

[0030] The present invention also provides carbon-based pumice prepared by the preparation method described in the above technical solution.

[0031] The invention provides a method for preparing carbon-based pumice, comprising the following steps: mixing a main material, a foaming agent, a foaming aid and water to obtain a slurry; the main material comprises a basic material and / or a silicon-aluminum ratio adjusting agent; the basic material comprises sludge or organic sludge; granulating the slurry to obtain spherical particles; spraying an aqueous solution of an air retaining agent on the surface of the spherical particles, and then foaming and drying in sequence to obtain a blank; performing a first sintering on the blank under a sealed condition to obtain a first sintered product; performing a second sintering on the first sintered product under a nitrogen atmosphere to obtain a second sintered product; activating the second sintered product to obtain the carbon-based pumice. The present invention uses basic materials and / or silicon-aluminum ratio blending agents as main materials, and adds foaming agents and foaming aids to generate a large number of bubbles during foaming, forming a large number of open pores and gaps inside the material, thereby improving the effective porosity of the carbon-based pumice; by using an air retaining agent, the material can be wrapped to prevent the bubbles generated during foaming from escaping quickly, thereby further improving the effective porosity of the carbon-based pumice; by using the principle of vapor deposition, sintering under sealed conditions can deoxidize CO generated by organic carbon and biochar into pure single carbon molecules, and at the same time, self-assemble in pre-fabricated gaps to form a honeycomb pipe bundle structure composed of carbon molecules, and these bundle-structured pipes have excellent adsorption and flowability; by activation, the honeycomb micron pipe bundle can be further strengthened, the effective porosity can be improved, thereby improving fluidity and greatly reducing the probability of blockage; by using sludge or organic sludge as the basic material and a small amount of auxiliary carbon source, a structure with silicon oxide as the main body and containing honeycomb carbon molecule pipe bundles connecting a large number of pores is prepared, while improving performance, reducing the use of a large amount of wood materials, saving raw material costs. Experimental results show that the effective porosity of the carbon-based pumice prepared by the present invention is 35-50%, the cylinder pressure strength is 0.5-2.8 MPa, and the electrical conductivity is 3.5-5 S / m. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a physical picture of the carbon-based pumice prepared in Example 1;

[0033] Figure 2 This is a SEM image of the carbon-based pumice prepared in Example 1;

[0034] Figure 3 This is a SEM image of the carbon-based pumice prepared in Example 1;

[0035] Figure 4 This is a comparison chart of the effluent of the carbon-based pumice prepared in Example 1 and the coconut shell activated carbon prepared in Comparative Example 2 after adsorbing domestic sewage for 1 hour;

[0036] Figure 5 This is a comparison chart of the effluent of the carbon-based pumice prepared in Example 1 and the coconut shell activated carbon prepared in Comparative Example 2 after adsorbing printing and dyeing wastewater for 1 hour;

[0037] Figure 6 The five positions of element detection of the carbon-based pumice carbon molecular pipeline bundle prepared in Example 1;

[0038] Figure 7 This is the EDS spectrum of the carbon-based pumice carbon molecular pipeline bundle position 1 prepared in Example 1;

[0039] Figure 8 This is the EDS spectrum of the carbon-based pumice carbon molecular pipeline bundle position 2 prepared in Example 1;

[0040] Fig. 9 This is the EDS spectrum of the carbon-based pumice carbon molecular pipeline bundle at position 3 prepared in Example 1;

[0041] Fig.10 This is the EDS spectrum of the carbon-based pumice carbon molecular pipeline bundle position 4 prepared in Example 1;

[0042] Fig.11 This is the EDS spectrum of the carbon-based pumice carbon molecular pipeline bundle at position 5 prepared in Example 1;

[0043] Fig.12 This is a schematic diagram of the test of the carbon-based pumice prepared in Examples 1 to 3;

[0044] Fig.13 The fluidity data of the carbon-based pumice prepared in Examples 1 to 3 are shown. DETAILED DESCRIPTION

[0045] The present invention provides a method for preparing carbon-based pumice, comprising the following steps:

[0046] (1) mixing a main material, a foaming agent, a foaming aid and water to obtain a slurry; the main material comprises a base material and / or a silicon-aluminum ratio adjusting agent; the base material comprises sludge or organic sludge;

[0047] (2) granulating the slurry obtained in step (1) to obtain spherical particles;

[0048] (3) spraying an aqueous solution of an air retaining agent onto the surface of the spherical particles obtained in step (2), and then foaming and drying the particles in sequence to obtain a blank;

[0049] (4) performing a first sintering on the blank obtained in step (3) under a sealed condition to obtain a first sintered product;

[0050] (5) subjecting the first sintered product obtained in step (4) to a second sintering in a nitrogen atmosphere to obtain a second sintered product;

[0051] (6) Activating the second sintered product obtained in step (5) to obtain carbon-based pumice.

[0052] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0053] The invention mixes the main material, the foaming agent, the foaming auxiliary agent and water to obtain the slurry.

[0054] In the present invention, the main ingredients include base materials and / or silicon-aluminum ratio adjusters.

[0055] In the present invention, the base material includes sludge or organic sludge; the particle size of the sludge is preferably 300 mesh; the silicon-aluminum ratio blending agent is preferably Al 4 [Si 4 O 10 ][OH] 8 The purity of the silicon-aluminum ratio adjusting agent is preferably above 95%; the particle size of the silicon-aluminum ratio adjusting agent is preferably 200-300 meshes. In the present invention, the main material is the matrix material.

[0056] In the present invention, the slurry is preferably further added with an auxiliary carbon source; the auxiliary carbon source is preferably coal powder, weeds or sawdust particles; the purity of the coal powder is preferably ≥95%; the particle size of the coal powder is preferably >200 mesh; the particle sizes of the weeds and sawdust particles are independently preferably >100 mesh; the auxiliary carbon source is preferably 1-10wt% of the mass of the main material, more preferably 5-8wt%. In the present invention, the auxiliary carbon source is used to provide a carbon source.

[0057] In the present invention, the auxiliary carbon source is preferably added simultaneously with the main material.

[0058] In the present invention, when the main material is the base material and the silicon-aluminum ratio blending agent, the base material is preferably 50-60% of the main material mass, more preferably 50-55%, and the silicon-aluminum ratio blending agent is preferably 40-50% of the main material mass, more preferably 45-50%. The present invention can further improve the effective porosity of the carbon-based pumice by controlling the mass of the base material and the silicon-aluminum ratio blending agent.

[0059] In the present invention, the foaming agent is preferably azodicarbonamide and / or polyurethane; the foaming agent is preferably 0.5-1.5% of the mass of the main material, more preferably 0.6-1.2%, and more preferably 0.8-1.0%. The present invention limits the amount of the foaming agent to the above range to further improve the adsorption performance of the carbon-based pumice.

[0060] In the present invention, the foaming aid is preferably at least one of calcium carbonate, calcium bicarbonate, aluminum chloride and phosphate starch; the mass ratio of the foaming aid to the foaming agent is preferably 1: 1. The present invention limits the mass ratio of the foaming aid to the foaming agent to 1: 1, which can further improve the adsorption performance of the carbon-based pumice.

[0061] The present invention has no particular limitation on the amount of water used, as long as the raw materials are dissolved.

[0062] In the present invention, the mixing of the main ingredients, the foaming agent, the foaming aid and water is preferably carried out in the following steps:

[0063] 1) ball-milling the foaming agent and the foaming aid to obtain a mixed material;

[0064] 2) mixing the mixture obtained in step 1) with water to obtain a mixed solution;

[0065] 3) Mixing the mixed solution obtained in step 2) with the main material.

[0066] In the present invention, the foaming agent and the foaming aid are preferably ball-milled to obtain a mixed material.

[0067] The present invention has no special limitation on the operation of ball milling, as long as the mixed material is processed to a size of <100 mesh.

[0068] After obtaining the mixed material, the present invention preferably mixes the mixed material with water to obtain a mixed solution.

[0069] The present invention has no special limitation on the operation of mixing the mixed material with water, as long as the raw materials are mixed evenly.

[0070] After obtaining the mixed solution, the present invention preferably mixes the mixed solution with the main material.

[0071] The present invention has no special limitation on the operation of mixing the mixed solution with the main material, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.

[0072] After the mixing is completed, the present invention preferably ages the mixed product to obtain a slurry.

[0073] In the present invention, the aging temperature is preferably room temperature; the aging time is preferably 12 to 24 hours, more preferably 15 to 24 hours. The present invention can fully infiltrate through aging.

[0074] After obtaining the slurry, the present invention granulates the slurry to obtain spherical particles.

[0075] The present invention has no particular limitation on the granulation operation, and any operation well known to those skilled in the art may be used.

[0076] In the present invention, the particle size of the spherical particles is preferably 0.5 to 1.0 cm.

[0077] After obtaining the spherical particles, the present invention sprays the aqueous solution of the air retaining agent on the surface of the spherical particles, and then sequentially performs foaming and drying to obtain the blank.

[0078] In the present invention, the gas retaining agent is preferably sodium silicate and / or methyl cellulose. The present invention uses the gas retaining agent to wrap the material and prevent the bubbles generated during foaming from escaping quickly, thereby further improving the effective porosity of the carbon-based pumice.

[0079] In the present invention, the concentration of the aqueous solution of the air retaining agent is preferably 1-3wt%, more preferably 1.5-2wt%; the mass of water in the air retaining agent is preferably 30-40% of the mass of the main material. The present invention limits the amount of the air retaining agent to the above range to further improve the effective porosity of the carbon-based pumice.

[0080] The present invention has no particular limitation on the operation of spraying the aqueous solution of the air retaining agent onto the surface of the spherical particles, and the operation well known to those skilled in the art can be adopted.

[0081] In the present invention, the foaming temperature is preferably 150-200°C, more preferably 160-180°C; the foaming time is preferably 30-60min, more preferably 40-50min, and most preferably 45min. The present invention can quickly increase the temperature by foaming at high temperature, so that the foaming agent can fully react in a short time to produce a large amount of pores and gaps composed of oxygen, carbon monoxide, carbon dioxide and some water vapor; the adsorption performance of the carbon-based pumice can be further improved by controlling the temperature and time of foaming.

[0082] The present invention has no special limitation on the drying operation, as long as the moisture content of the blank is controlled below 10%.

[0083] After obtaining the blank, the present invention performs a first sintering on the blank under a sealed condition to obtain a first sintered product.

[0084] In the present invention, the first sintering is preferably carried out in a reduction type sintering furnace. The present invention has no special limitation on the type of the reduction type sintering furnace, and any equipment well known to those skilled in the art can be used.

[0085] In the present invention, the temperature of the first sintering is preferably 1000-1200°C, more preferably 1050-1150°C, and most preferably 1100°C; the time of the first sintering is preferably 90-120 minutes, and more preferably 100 minutes. The sintering in a sealed condition of the present invention can deoxidize the organic carbon and enter the reduction reaction stage, generating free carbon molecules, CO and CO 2 gas.

[0086] After obtaining the first sintered product, the present invention performs a second sintering on the first sintered product under a nitrogen atmosphere to obtain a second sintered product.

[0087] In the present invention, the temperature of the second sintering is preferably 1000-1200°C, more preferably 1050-1150°C, and most preferably 1100°C; the time of the second sintering is preferably 30-60 minutes, and more preferably 40-50 minutes. The second sintering is performed in a nitrogen atmosphere, so that the CO generated by the first sintering is cracked, the CO bond is broken, and the CO is decomposed into C and O atoms, further forming a large number of carbon molecules and CO 2 Gas, carbon molecules can self-assemble in pre-fabricated gaps to form a honeycomb pipe bundle structure composed of carbon molecules. These bundle-like biocarbon pipes give the material excellent adsorption, fluidity and conductivity.

[0088] After obtaining the second sintered product, the present invention activates the second sintered product to obtain carbon-based pumice.

[0089] In the present invention, the activator used for the activation is preferably an aqueous solution of at least one of biological acid, sodium lauryl sulfate, fatty alcohol polyoxyethylene ether and alkyl glycoside; the biological acid is preferably citric acid, polylactic acid or itaconic acid.

[0090] In the present invention, the mass concentration of the activator is preferably 3-5%, more preferably 3.5-4.0%. The present invention has no particular limitation on the amount of the activator, as long as the second sintered product is completely immersed in the activator.

[0091] In the present invention, the activation temperature is preferably room temperature; the activation time is preferably 15 to 30 minutes. The present invention can wash out impurities (nitrogen, phosphorus, potassium, calcium oxide, dust, etc.) in the material through activation, further activate the carbon microtubes, improve the adsorption efficiency, and form a honeycomb carbon microtube bundle material composed of pure silicon oxide and carbon microtubes.

[0092] The present invention uses basic materials and / or silicon-aluminum ratio blending agents as main materials, and adds foaming agents and foaming aids to generate a large number of bubbles during foaming, forming a large number of open pores and gaps inside the material, thereby improving the effective porosity of the carbon-based pumice. By adopting an air retaining agent, the material can be wrapped to prevent the bubbles generated during foaming from escaping quickly, thereby further improving the effective porosity of the carbon-based pumice. By utilizing the principle of vapor deposition, sintering under sealed conditions can deoxidize CO generated by organic carbon and biochar into pure single carbon molecules, and at the same time, self-assemble in pre-fabricated gaps to form a honeycomb pipe bundle structure composed of carbon molecules, and these bundle-structured pipes have excellent adsorption and flowability. Through activation, the honeycomb micron pipe bundle can be further strengthened, the effective porosity can be improved, thereby improving fluidity and greatly reducing the probability of blockage. By adopting sludge or organic sludge as the basic material and a small amount of auxiliary carbon source, a structure with silicon oxide as the main body and containing honeycomb carbon molecule pipe bundles connecting a large number of pores is prepared, which reduces the use of a large amount of wood materials while improving performance, saving raw material costs.

[0093] The main raw material of the present invention is sludge or organic sludge, and Al 4 [Si 4 O 10 ][OH] 8 It is a silicon-aluminum blending agent, with organic carbon in sludge or organic sludge as the main carbon source, and an auxiliary carbon source is added. The final product is a porous material with silicon oxide as the main material, aluminum oxide as the auxiliary material, and containing biocarbon microtubes as conduits and a large number of micropores. Since the raw material silicon oxide is a basic material that is very easy to obtain, and a large number of carbon microtube bundles are manufactured by reducing organic carbon in nature, the cost is greatly reduced, and at the same time, higher adsorption and conductivity can be achieved than common activated carbon.

[0094] The present invention also provides carbon-based pumice prepared by the preparation method described in the above technical solution.

[0095] The carbon-based pumice provided by the present invention has electrical conductivity of 3.5-5S / m, which is several to dozens of times the electrical conductivity of coconut shell activated carbon (0.1-1S / m), and is a semiconductor non-metallic material with good electrical conductivity; it contains honeycomb carbon micron tube bundles with a mass ratio of about 5% and a volume ratio of 20-25%; and contains a large number of micropores with a volume ratio of 40-50%.

[0096] In the present invention, the shape of the carbon-based pumice is preferably porous block, brecciated, spherical or columnar; the color of the carbon-based pumice is preferably dark grey or black.

[0097] The carbon-based pumice provided by the present invention has various short-term adsorption capacities for organic matter in water bodies that are much higher than coconut shell activated carbon; it has good stability under natural conditions, and has the characteristics of high-intensity water adsorption and slow release of adsorbed water; its internal structure is characterized by the combination of carbon microtubes with a honeycomb pipe bundle structure and a large number of pores; the pores have a diameter of 0.2 to 2 mm and are densely distributed; the pores are mainly polygonal in shape, and there are also a small number of elliptical shapes; the pores are completely closed by the outer wall to form closed pores; it has strong weathering resistance and no aging phenomenon.

[0098] The performance parameters of the carbon-based pumice provided by the present invention are as follows:

[0099] Bulk density: 0.33-0.67 tons / cubic meter

[0100] Conductivity: 3.5~5S / m

[0101] Specific surface area: ≥50cm 2 / g

[0102] Effective porosity: 35-50%

[0103] Cylinder pressure strength: 0.5~2.8MPa / cm 2

[0104] Particle size: 5-10mm or 10-15mm.

[0105] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0106] The sludge used in the embodiment is the bottom mud (200-300 mesh) in the natural lake in Huizhou, Guangdong. The organic carbon content is about 5-10 wt % after testing.

[0107] Example 1

[0108] A method for preparing carbon-based pumice comprises the following steps:

[0109] (1) The sludge and the silicon-aluminum ratio blending agent are mixed in a mass percentage of 1:1 to obtain a batch 1; wherein the silicon-aluminum ratio blending agent is Al 4 [Si 4 O 10 ][OH] 8 ; The purity of the silicon-aluminum ratio blending agent is above 95%, and the particle size is 200-300 mesh;

[0110] (2) mixing 5% by mass of ingredient 1 with wood chips particles of auxiliary carbon source of 200 mesh or larger with ingredient 1 to obtain ingredient 2;

[0111] (3) mixing 1% by weight of azodicarbonamide in ingredient 1 and 1% by weight of phosphate starch in ingredient 1, and processing in a ball mill to a size of <100 mesh to obtain ingredient 3;

[0112] (4) Ingredient 3 is added to 30% of the mass of ingredient 1 in water to prepare an aqueous solution, which is then mixed with ingredient 2 to form a slurry, and then aged at room temperature for 24 hours, and then placed in a disc granulator to form spherical particles with a diameter of 0.5 to 1.5 cm;

[0113] (5) Methyl cellulose is added to 30% of water in ingredient 1 to prepare a 1.5% air retaining agent aqueous solution, and then the air retaining agent solution is atomized and sprayed on the surface of the spherical particles, and then foamed at 180° C. for 30 minutes, and then dried to obtain a blank with a water content of less than 10%;

[0114] (6) transporting the blank to a reduction type sintering furnace via a conveyor belt and sintering at 1100° C. under a sealed condition for 100 min to obtain a first sintered product;

[0115] (7) Nitrogen gas is introduced into the furnace and the steel is sintered at 1100° C. for 30 minutes to obtain a second sintered product.

[0116] (8) The second sintered product is immersed in a citric acid aqueous solution with a mass concentration of 5% for activation to obtain a carbon-based pumice, wherein the activation temperature is room temperature and the activation time is 15 minutes.

[0117] Example 2

[0118] A method for preparing carbon-based pumice comprises the following steps:

[0119] (1) A silicon-aluminum ratio adjusting agent is mixed with 10% by weight of an auxiliary carbon source coal powder with a mesh size of 300 or more to obtain a batch 1; wherein the silicon-aluminum ratio adjusting agent is Al 4 [Si 4 O 10 ][OH] 8 ; The purity of the silicon-aluminum ratio blending agent is above 95%, and the particle size is 200-300 mesh; the purity of the coal powder is 95%;

[0120] (2) mixing polyurethane with a silicon-aluminum ratio of 0.5% by weight of the mixing agent and calcium bicarbonate with a silicon-aluminum ratio of 0.5% by weight of the mixing agent, and processing in a ball mill to a size of <100 mesh to obtain ingredient 2;

[0121] (4) Ingredient 2 is placed in water with a silicon-aluminum ratio of 30% by mass of the formulation agent to prepare an aqueous solution, which is then mixed with ingredient 1 to form a slurry, and then aged at room temperature for 24 hours, and then placed in a disc granulator to produce spherical particles with a diameter of 0.5 to 1.5 cm;

[0122] (5) sodium silicate is added to water containing 30% of the mass of the silicon-aluminum ratio preparation agent to prepare a 2% concentration of the air retaining agent aqueous solution, and then the air retaining agent solution is atomized and sprayed on the surface of the spherical particles, and then foamed at 180° C. for 60 minutes, and then dried to obtain a blank with a water content of less than 10%;

[0123] (6) transporting the blank to a reduction type sintering furnace via a conveyor belt and sintering at 1200° C. under a sealed condition for 120 min to obtain a first sintered product;

[0124] (7) nitrogen gas is introduced into the furnace body and sintered at 1200° C. for 30 min to obtain a second sintered product;

[0125] (8) The second sintered product is immersed in an aqueous solution of sodium dodecyl sulfate with a mass concentration of 5% for activation to obtain a carbon-based pumice, wherein the activation temperature is room temperature and the activation time is 20 minutes.

[0126] Example 3

[0127] (1) 0.5% of azodicarbonamide by weight of sludge and 0.5% of phosphate starch by weight of sludge were mixed and placed in a ball mill to process the mixture to a size of less than 100 meshes to obtain ingredient 1;

[0128] (2) ingredient 1 is placed in water with a mass content of 30% of the sludge to prepare an aqueous solution, which is then mixed with the sludge to form a slurry, and then aged at room temperature for 24 hours, and then placed in a disc granulator to form spherical particles with a diameter of 0.5 to 1.5 cm;

[0129] (3) Methyl cellulose is added to water with a mass content of 30% of the sludge to prepare a 1.0% air retaining agent aqueous solution, and then the air retaining agent solution is atomized and sprayed on the surface of the spherical particles, and then foamed at 180° C. for 45 minutes, and then dried to obtain a blank with a water content of less than 10%;

[0130] (4) transporting the blank to a reduction type sintering furnace via a conveyor belt and sintering at 1100° C. under a sealed condition for 90 minutes to obtain a first sintered product;

[0131] (5) Nitrogen is introduced into the furnace and the steel is sintered at 1100° C. for 30 minutes to obtain a second sintered product.

[0132] (6) The second sintered product is immersed in a citric acid aqueous solution with a mass concentration of 3% for activation to obtain a carbon-based pumice, wherein the activation temperature is room temperature and the activation time is 30 minutes.

[0133] Comparative Example 1

[0134] Artificial pumice is made by other companies according to common standards, with a particle size of 10 to 20 mm and a market price of about RMB 6,000 per cubic meter.

[0135] Comparative Example 2

[0136] Coconut shell activated carbon is commonly used by other companies to produce activated carbon for water treatment. The particle size is 5 to 15 mm and the market price is 12,000 RMB per cubic meter.

[0137] The materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to performance tests, and the results are shown in Tables 1 and 2; wherein, the carbon content was detected by standard elemental analysis; the effective porosity was tested by a standard immersion method (measured with clean water at room temperature and pressure, and the calculation formula for the effective porosity is shown in Formula I); the cylinder compressive strength was tested by the national standard GB2842-81 "Test Method for Light Aggregate"; and the conductivity was tested by a ST2258C four-probe tester.

[0138] Table 1 Performance data of carbon-based pumice prepared in Examples 1 to 3

[0139] Item (average) Example 1 Example 2 Example 3 Carbon content (mass ratio) 5% 5.5% 3% Effective porosity 50% 40% 35% Cylinder pressure strength 1MPa 2.8MPa 0.5MPa

[0140] Table 2 Performance data of materials prepared in Example 1 and Comparative Examples 1-2

[0141] project Example 1 Comparative Example 1 Comparative Example 2 Effective porosity 50% 15% 35% Conductivity 4.3S / m NA 0.8S / m Cylinder pressure strength 1MPa 1.8MPa 0.6MPa

[0142] The calculation formula of the effective porosity of the filter material at room temperature is shown in Formula I and described by volume ratio:

[0143]

[0144] In the formula, m1 is the mass of the material when dry, m2 is the mass of the material after saturation with water, and V1 is the volume of the material.

[0145] It can be seen from Tables 1 and 2 that the effective porosity and electrical conductivity of the carbon-based pumice prepared by the present invention are greatly improved, so the adsorption performance is improved several times.

[0146] The actual picture of the carbon-based pumice prepared in Example 1 is as follows Figure 1 shown.

[0147] from Figure 1 It can be seen that the carbon-based pumice prepared in the example is spherical.

[0148] The SEM images of the carbon-based pumice prepared in Example 1 at different magnifications are as follows: Figure 2 and 3 shown.

[0149] from Figure 2 and 3 It can be seen that the prepared carbon-based pumice is a morphology combining through-type carbon nanotubes and pores.

[0150] The adsorption performance of the carbon-based pumice prepared in Example 1 and the coconut shell activated carbon prepared in Comparative Example 2 was tested. The results are as follows: Figure 4 and 5 As shown, Figure 4 This is a comparison chart of the effluent of the carbon-based pumice prepared in Example 1 and the coconut shell activated carbon prepared in Comparative Example 2 after adsorbing domestic sewage for 1 hour; Figure 5 This is a comparison chart of the effluent from the carbon-based pumice prepared in Example 1 and the coconut shell activated carbon in Comparative Example 2 after adsorbing printing and dyeing sewage for 1 hour (the testing equipment uses a Hach 3900 spectrophotometer and Hach standard reagents; the domestic sewage is the domestic sewage from the residential area sampled in Boluo County, Huizhou (COD: 269 mg / L; ammonia nitrogen: 15 mg / L; total phosphorus: 20.25 mg / L; total nitrogen: 84.7 mg / L); the printing and dyeing sewage is the printing and dyeing sewage used in the internal pool of the printing and dyeing factory in Boluo County, Huizhou (COD: 549 mg / L, ammonia nitrogen: 5.2 mg / L, total phosphorus: 9.01 mg / L, total nitrogen: 12.4 mg / L); the simulated aerated biological filter effluent mode is adopted, with sewage entering from the bottom and exiting from the top, and 1 hour of effluent).

[0151] from Figure 4 and 5 It can be seen that the short-time adsorption capacity of the carbon-based pumice provided by the present invention in water treatment is several times that of other products, which can greatly improve the water output effect in water treatment and greatly shorten the time of water treatment.

[0152] The carbon-based pumice prepared in Example 1 was subjected to a component analysis test, wherein the instrument model was an X-ray fluorescence spectrometer ARL Perform'X, and the instrument number was 21003415; the test was based on JY / T0569-2020 General Rules for Wavelength Dispersion X-ray Fluorescence Spectrometry Analysis Methods; the test method was to add the carbon-based pumice and boric acid into a tablet press, press them into a round block with a diameter of 40 mm, a thickness of 3 mm, and a smooth and flat surface, and then put the round block into a sample holder, put it into the instrument sample position, fill in the sample information on the instrument software, start the test, and export the test data after the test is completed. The XRF component analysis results show that the main component is SiO 2 、Al 2 O 3 , K 2 O, Fe 2 O 3 , the contents are 51.83%, 38.7%, 3.42% and 2.89% respectively.

[0153] The five positions (such as Figure 6 As shown) for element detection, the results are as follows Figures 7 to 11 As shown in Tables 3 to 7, Figure 7 This is the EDS spectrum of the carbon-based pumice carbon molecular pipeline bundle position 1 prepared in Example 1; Figure 8 This is the EDS spectrum of the carbon-based pumice carbon molecular pipeline bundle position 2 prepared in Example 1; Fig. 9 This is the EDS spectrum of the carbon-based pumice carbon molecular pipeline bundle at position 3 prepared in Example 1; Fig.10 This is the EDS spectrum of the carbon-based pumice carbon molecular pipeline bundle position 4 prepared in Example 1; Fig.11 This is the EDS energy spectrum of position 5 of the carbon-based pumice carbon molecular pipeline bundle prepared in Example 1.

[0154] Table 3 Element content at position 1 in the carbon-based pumice carbon molecular tube bundle prepared in Example 1

[0155]

[0156]

[0157] Table 4 Element content of position 2 in the carbon-based pumice carbon molecular pipeline bundle prepared in Example 1

[0158] element Wt% At% C 79.21 91.82 O 2.49 2.16 Al 2.24 1.16 Si 2.25 1.12 P 0.37 0.17 S 0.25 0.11 K 1.33 0.47 Ca 0.35 0.12 Fe 11.51 2.87 Total 100.00 100.00

[0159] Table 5 Element content at position 3 in the carbon-based pumice carbon molecular pipeline bundle prepared in Example 1

[0160] element Wt% At% C 91.16 94.60 O 5.60 4.36 Al 0.61 0.28 Si 0.52 0.23 S 0.11 0.04 K 0.42 0.13 Fe 1.58 0.36 Total 100.00 100.00

[0161] Table 6 Element content at position 4 in the carbon-based pumice carbon molecular pipeline bundle prepared in Example 1

[0162]

[0163]

[0164] Table 7 Element content at position 5 in the carbon-based pumice carbon molecular pipeline bundle prepared in Example 1

[0165] element Wt% At% C 54.55 82.03 O 1.10 1.24 Al 2.41 1.61 Si 3.53 2.27 P 0.36 0.21 K 0.58 0.27 Ca 1.99 0.90 Fe 35.48 11.47 Total 100.00 100.00

[0166] from Figures 7 to 11 It can be seen from Tables 3 to 7 that the main component of the honeycomb carbon molecular pipeline bundles of the carbon-based pumice prepared by the present invention is carbon element.

[0167] Fluidity test (simulating BAF aerated biological filter):

[0168] The fluidity of the carbon-based pumice prepared in Examples 1 to 3 was tested. A water pump was used to inject water into the bottom of the container at a fixed height through a pipe inserted at the bottom with the same power using a water pump. The total amount of water flow and the time when the water level reached the four standard positions of the container were measured by a floor scale and a timer to calculate the flow rate of water in the space filled with different particles. The two modes of this test were: no material filling and 5-10 mm particles filling; in the mode of no filler filling, 4.15 m took 1 hour, and the water volume test was 302 kg. The test method is as follows: Fig.12 shown.

[0169] The flowability data of the carbon-based pumice prepared in Examples 1 to 3 are as follows: Fig.13 shown.

[0170] from Fig.13 It can be seen that the probability of clogging of the carbon-based pumice prepared by the present invention is greatly reduced; the loss of liquid flowing inside is very small, almost no loss.

[0171] It can be seen from the above embodiments and comparative examples that the carbon-based pumice prepared by the preparation method provided by the present invention has excellent adsorption performance, fluidity and conductivity, and the cost is greatly reduced.

[0172] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing carbon-based pumice, comprising the following steps: (1) mixing a main material, a foaming agent, a foaming aid and water to obtain a slurry; the main material comprises a base material and / or a silicon-aluminum ratio adjusting agent; the base material comprises sludge or organic sludge; (2) granulating the slurry obtained in step (1) to obtain spherical particles; (3) spraying an aqueous solution of an air retaining agent onto the surface of the spherical particles obtained in step (2), and then foaming and drying the particles in sequence to obtain a blank; (4) performing a first sintering on the blank obtained in step (3) under a sealed condition to obtain a first sintered product; (5) subjecting the first sintered product obtained in step (4) to a second sintering in a nitrogen atmosphere to obtain a second sintered product; (6) Activating the second sintered product obtained in step (5) to obtain carbon-based pumice.

2. The preparation method according to claim 1, characterized in that: The silicon-aluminum ratio adjusting agent in step (1) is Al4[Si4O 10 ][OH]8, the purity of the silicon-aluminum ratio adjusting agent is above 95%, and the particle size of the silicon-aluminum ratio adjusting agent is 200-300 mesh.

3. The preparation method according to claim 1, characterized in that: In the step (1), the foaming agent is azodicarbonamide and / or polyurethane, and the foaming agent accounts for 0.5-1.5% of the mass of the main material.

4. The preparation method according to claim 1, characterized in that: In the step (1), the foaming aid is at least one of calcium carbonate, calcium bicarbonate, aluminum chloride and phosphate starch, and the mass ratio of the foaming aid to the foaming agent is 1:

1.

5. The preparation method according to claim 1, characterized in that: In the step (3), the air retaining agent is sodium silicate and / or methyl cellulose, and the mass concentration of the aqueous solution of the air retaining agent is 1-3%.

6. The preparation method according to claim 1, characterized in that: The foaming temperature in step (3) is 150-200° C., and the foaming time is 30-60 min.

7. The preparation method according to claim 1, characterized in that: In the step (4), the temperature of the first sintering is 1000-1200° C., and the time of the first sintering is 90-120 minutes.

8. The preparation method according to claim 1, characterized in that: In the step (5), the temperature of the second sintering is 1000-1200° C., and the time of the second sintering is 30-60 minutes.

9. The preparation method according to claim 1, characterized in that: The activator used for activation in step (6) is an aqueous solution of at least one of biological acid, sodium lauryl sulfate, fatty alcohol polyoxyethylene ether and alkyl glycoside.

10. The carbon-based pumice prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Ceramic material with multi-stage duct structure and manufacture method thereof

    CN101885620A

  • Preparation method of modified activated carbon capable of simultaneously removing heavy metals and organic matters in sewage

    CN108479698A

  • Carbon product nano spar

    CN112058223A

  • Sludge-based activated carbon, preparation method thereof and application of sludge-based activated carbon in field of flue gas adsorption

    CN115716647A

  • Porous composite mineral water purification material and preparation method thereof

    CN117816123A

Cited By

  • Carbon-based pumice and preparation method therefor

    WO2026108659A1